Optical characterization of lithium fluoride thin-film imaging detectors for monochromatic hard X-rays. (1st April 2023) - Vincenti, M.A.; Montereali, R.M.; Nichelatti, E.; Nigro, V.; Piccinini, M.; Koenig, M.; Mabey, P.; Rigon, G.; Dabrowski, H.J.; Benkadoum, Y.; Mercere, P.; Da Silva, P.; et al.
Abstract: Lithium fluoride (LiF) crystals and thin films have been successfully investigated as X-ray imaging detectors based on optical reading of visible photoluminescence emitted by stable radiation-induced F2 and F3 + colour centres. In this work, the visible photoluminescence response of optically-transparent LiF film detectors of three different thicknesses, grown by thermal evaporation on Si(100) substrates and irradiated with monochromatic 7 keV X-rays at several doses in the range between 13 and 4.5× 10 3 Gy, was carefully investigated by fluorescence optical microscopy. For all the film thicknesses, the photoluminescence response linearly depends on the irradiation dose in the investigated dose range. The lowest detected dose, delivered to the thinnest LiF film, only 0.5 μm thick, is estimated 13 Gy. Edge-enhancement imaging experiments, conducted by irradiating LiF film detectors at the same energy placing an Au mesh in front of them at a distance of 15 mm, allowed estimating a spatial resolution of (0.38 ± 0.05) μm, which is comparable to the microscope one. This very high spatial resolution in LiF film radiation detectors based on colour centres photoluminescence is combined with the availability of a wide field of view on large areas.